Comprehensive identification of key compounds in different quality grades of soy sauce-aroma type baijiu by HS-SPME-GC-MS coupled with electronic nose - Wu, Junhai; Chen, Renyuan; Li, Xiaobo; Fu, Zheyang; Xian, Chun; Zhao, Wenwu; Zhao, Cheng; Wu, Xinying (Frontiers in Nutrition, 2023)
In the production of Moutai-flavor liquor (MFL), the quality of base liquor significantly impacts the final product's quality. And the low-quality liquor may cause health problems. The different quality grades base liquors were analyzed to investigate the relationship between quality and key compounds in MFL. First, by sensory evaluation, the sauce, floral and fruity, fermented aromas and taste indicators (softness, fullness, harmony, purity and persistence) were positively correlated with the quality grade of base liquors. The electronic nose (E-nose) could distinguish the different quality grade base liquors well. It was found that the higher quality grade of the base liquors, the richer the content of aromatics, alcohols, aldehydes and ketones. Second, differential compounds were identified via untargeted metabolome based on the headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS). 16 common differential compounds were shared in the base liquor at different fermentation rounds, including 11 esters, 1 alcohol, 2 aldehydes and 2 ketones. At last, by correlation analysis of differential compounds and sensors responses of E-nose, furfuryl ethyl ether, butanoic acid ethyl ester, isopentyl hexanoate, nonanoic acid ethyl ester and 3-methyl-1-butanol had a significant effect on the response intensity of E-nose sensors. Thus, quantitative data on sensory differences of base liquor can be realized.